The importance of emotions in academic tourism: Application of a facial recognition software with Erasmus students - Picazo Peral, Patricia; Lam González, Yen E. (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
This paper analyses the importance of the emotional content in the communication campaigns of universities to attract students for a research stay. To do so, 201 Spanish students that have finalised their Erasmus internships were interviewed. Besides, a biometric experiment was carried out with the Noldus Face Reader software that analyzes facial expressions. As a result, it was found that the prestige of the university is not so relevant, being the transmission of emotions of happiness considered the most important element for students when choosing a university. The results and their usefulness for the educational marketing are discussed in a dedicated section.